Kotahi te moana, only one ocean: Pacific environmentalism, 1970–1995 - de Jong, MH (2022)

(untitled)
“Pacific environmentalism” emerged as a regional ethic connecting Oceania and protecting Pacific peoples’ ways of thinking and relating to the natural world. It combined a customary body of knowledge about Pacific ecologies shaped over centuries, with decolonial politics, international science, and regional principles. This thesis considers the place of Pacific environmentalism within Pacific societies and the global environmental movement from 1970–1995. It argues that Pacific people consolidated knowledge about their ocean and islands, specifically that they are interconnected, indigenous, and inviolable, and used this to further self-determination—first as part of a regional movement, and then to make global interventions.